Floristic Composition And Economic Valuation Of 2-Ha Plots Of Hill Forest In Langkawi - Dahalan, Mohd Puat (2013)
Floristic composition data are a valuable tool in sustainable forest and environmental management. A 2.0-ha permanent plot (200 m x 100 m) located between 300 and 750 m a.s.l. was each established at Gunung Matchingchang Forest Reserve (GMFR) and Gunung Raya Forest Reserve (GRFR) in Langkawi for the purpose of inventoring hill floral diversity. The research sites comprised of two 2.0-ha plots each of which was located in GMFR and GRFR and was further divided into fifty 20 m x 20 m subplots. In GM_FR and GRFR, there were a total of 12,530 trees and 7,967 trees respectively. All trees with abundant species, family, diameter breast height (DBH), total biomass (TB) and stumpage value were identified, assessed and recorded. The largest species in GMFR was recorded by Hydnocarpus filipes (Flacoutiaceae) with as many as 2,591 individuals. In GRFR, Diospyros ismailii (Ebenaceae) recorded the highest number with 799 individuals.